Land Use and Land Cover Change Strongly Modulates Land‐Atmosphere Coupling and Warm‐Season Precipitation Over the Central United States in CESM2‐VR. (18th September 2020) - Devanand, Anjana; Huang, Maoyi; Lawrence, David M.; Zarzycki, Colin M.; Feng, Zhe; Lawrence, Peter J.; Qian, Yun; Yang, Zhao
Abstract: Prior research indicates that land use and land cover change (LULCC) in the central United States has led to significant changes in surface climate. The spatial resolution of simulations is particularly relevant in this region due to its influence on model skill in capturing mesoscale convective systems (MCSs) and on representing the spatial heterogeneity. Recent advances in Earth system models (ESMs) make it feasible to use variable resolution (VR) meshes to study regional impacts of LULCC while avoiding inconsistencies introduced by lateral boundary conditions typically seen in limited area models. Here, we present numerical experiments using the Community Earth System Model version 2–VR to evaluate (1) the influence of resolution and land use on model skill and (2) impacts of LULCC over the central United States at different resolutions. These simulations are configured either on the 1° grid or a VR grid with grid refinement to 1/8° over the contiguous United States for the period of 1984–2010 with two alternative land use data sets corresponding to the preindustrial and present day states. Our results show that skill in simulating precipitation over the central United States is primarily dependent on resolution, whereas skill in simulating 2‐m temperature is more dependent on accurate land use. The VR experiments show stronger LULCC‐induced precipitation increases over the Midwest in May and June, corresponding to an increase in the number of MCS‐like features and a more conductive thermodynamic environment for convection. Our study demonstrates the potential of using VR ESMs for hydroclimatic simulations in regions with significant LULCC. Plain Language Summary: Land use and land cover change (LULCC) in the central United States has likely affected the historical climate of this region, along with other global and regional factors. Experiments using Earth system models can be used to understand how LULCC has affected the regional climate. But such studies are limited by model resolution used for the experiments. Recent developments in Earth system modeling allow for higher regional resolution simulations over areas of focused interest in global simulations. In this study, we perform model experiments using the Community Earth System Model at a high resolution over the central United States to understand how resolution affects the model skill and the simulated LULCC impacts. The warm‐season precipitation over the central United States shows lower biases in the high‐resolution simulations. We also find stronger precipitation increases over the Midwest during May and June due to LULCC in experiments at high resolution. This is because the environmental conditions over the Midwest become more favorable for convective activities as a result of LULCC in the high‐resolution experiments. Key Points: Precipitation and temperature biases over the central United States are reduced with more accurate land use and higher resolution in VR‐CESM The high‐resolution model shows stronger LULCC‐induced precipitation increases over the Midwest in May and June Variable resolution model demonstrates great potential to be used for regional hydroclimatic applications in areas of major LULCC